STRATEGI KOMUNIKASI DIGITAL BALAI PELESTARIAN CAGAR BUDAYA SULAWESI SELATAN DALAM MENINGKATKAN KUNJUNGAN WISATAWAN, STUDI KASUS: FORT ROTTERDAM - Soraya Firdausy; Ibnu Qayyim Na'iem; Yusmanizar; Nasrullah (Jurnal Dakwah Tabligh, 2022)
Tourism in Indonesia continues to be managed seriously by the Indonesian government in order to improve and develop tourism objects in Indonesia with the aim and purpose of none other than increasing the number of tourist visits from both foreign and domestic tourists. Tourism in Indonesia itself is managed by the Indonesian Ministry of Tourism which has the branding "Wonderful Indonesia" which is intended for foreign tourists and "Pesona Indonesia" which is aimed at domestic tourists. Pesona Indonesia on YouTube uses a digital campaign that is supported by the use of endorsements in the form of artists or vloggers to increase audience interest, whether watching videos on YouTube or taking trips. Tourism is one of the potential fields in terms of the development of a country, this is because tourism is considered capable of having a positive impact as a driver of people's economic activities. The most positive impact is that tourism plays an important role as a driver of economic growth and prosperity in terms of development in an area. Makassar City itself has a variety of tourism potential, ranging from natural, cultural, and artificial tourism to special interest tours, that's why many local and foreign tourists visit Makassar City. One of them is a historical heritage tourist attraction, namely Fort Rotterdam. The Cultural Conservation Preservation Center (BPCB) is a technical implementing unit of the Ministry of Education and Culture in the field of cultural heritage preservation which is under and responsible to the Director General of Culture. BPCB is in charge of protecting, developing, and utilizing cultural heritage and suspected cultural heritage in its working area. BPCB South Sulawesi as the management unit of Fort Rotterdam must know very well how to disseminate information about cultural sites, especially in the digital era. The main factor that must be considered to increase interest in visiting is to formulate and implement a targeted communication strategy, because the key to all human activities is communication, and strategy is the right way to deal with all these activities in order to achieve goals and remove obstacles. resolve. Although there are many tourist attractions in Makassar, if foreign tourists do not know this information, they will not be able to enjoy the development of tourism. This study uses descriptive qualitative research, using observation and interviews as data collection techniques. The data analysis process is carried out by examining all available data from various sources, namely observations, interviews, personal documents, and official documents. Then check the validity of the data using data triangulation and technical triangulation. The results show that the communication strategy of the South Sulawesi Cultural Heritage Preservation Center uses four stages, namely introducing the audience to determine the target of the communication strategy to be carried out, compiling messages, using informative and repetition methods, and utilizing the media as a means of disseminating information through Public Service and Publication Working Group. Supporting and inhibiting factors are also factors that affect the effectiveness of the communication strategy of the South Sulawesi Cultural Heritage Preservation Center.